Synthesis of Some New Saturated Butyrolactones - Makhloga Vimal Kukreti, P.S.; Chamoli, R.P. (Asian Journal of Chemistry, 2010)
γ-Oxoacids, β-(4-methylbenzoyl) propionic acid and β-(2,5- dimethylbenzoyl) propionic acid undergo condensation with various phenolic compounds in presence of concentrated sulphuric acid to give some new γ-butyrolactones in which γ-carbon atom is attached to two different phenyl rings. Structures of these compounds have been established on the basis of elemental analysis, chemical reactions and IR spectral data.